ANALISIS PERKEMBANGAN USAHA DANDELLION MENGGUNAKAN PENDEKATAN BUSINESS MODEL CANVAS - Abdullah Hammam,; Reza Widhar Pahlevi, (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2022)
Dandelion is a business engaged in the field of animal accessories, especially pets such as rabbits, guinea pigs, birds, cats and dogs. Dandelion was founded in mid-2020, at the beginning of its establishment this company only sold broiler rabbits for the products offered, so then Dandelion changed the products it sold with a focus on selling cage products only. This is due to the decrease in consumer interest in buying products (rabbits) from dandelions. This study aims to analyze internal (strengths and weaknesses) and external (opportunities and threats) factors by using the Strengths-Weaknesses-Opportunities-Threats (SWOT) Analysis tool that can affect Dandellion's business, formulate business development strategies, and develop model development. Dandellion's business uses the Business Model Canvas (BMC) approach which is composed of nine blocks, namely customer segment, value proposition, customer relationship, key partnership, key activities, key resources and cost structure as well as revenue stream. The BMC approach is needed as a visualization tool for efforts to develop Dandellion's business development strategies to optimize business services.